Electrochemical reduction of nitrogen to ammonia: progress, challenges and future outlook - Lee, Carmen (2022)
Ammonia is an important chemical used in the production of fertilizers. The electrochemical nitrogen reduction reaction (NRR) to synthesize ammonia has emerged to be a potential alternative approach. Here, we provide a short opinion of the current progress and challenges of nitrogen reduction reaction from the recent literature. Different types of electrocatalysts with their performances and design principles are briefly outlined. However, most of the electrocatalysts showed unsatisfactory catalytic performance for NRR because of various factors, such as the competing side reactions and the large thermodynamic energy barrier. Hence, the concept of conducting NRR should be re-evaluated. We provide our opinion on the future possible outlook on how to improve the NRR performance. Alternative external energy input should be coupled with the electrochemical reduction of nitrogen to help with the activation of nitrogen to ammonia. Some possible energy input could be the use of cold plasma and surface plasmon resonance.